Flexible bronchoscopic management of high post-intubation tracheal stenosis: a case series - Chopra, Manu; Sarkar, Saikat; Tyagi, Rahul; Kislay, Kishore; Tripathi, Srishti; Jagtap, Kiran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Post-intubation tracheal stenosis (PITS) affecting the upper 5 cm of the trachea, is difficult to manage because of its proximity to the vocal cords and the higher risks associated with surgery. Flexible bronchoscopic procedures provide a minimally invasive option for patients who are unsuitable for operative treatment. We describe a retrospective case series evaluating the outcomes of flexible bronchoscopic management in six patients with high PITS treated at a tertiary care chest centre of the Indian Armed Forces. Over a mean follow-up exceeding three years, all surviving patients remained symptom-free. This case series suggests that flexible bronchoscopic management is a safe and effective option for selected patients with high PITS and may represent a reasonable alternative when surgical treatment is not feasible.